Administrative Orientation and International Performance - Davidson, William H. (Journal of International Business Studies, 1984)
A recent trend in international management research has been the development of contingency models that identify optimal planning and management modes for international business units, given key characteristics of the product, market, and industry. In practice, however, planning and management modes appear to be dictated not only by external market and industry conditions, but also by internal aspects of the firm's administrative orientation. The intent of this paper is to examine how aspects of the firm's administrative orientation influence the choice of management modes, and to examine how the choice of management modes impacts international performance.